Characterization and Applications of the Pectin Extracted from the Peel of Passiflora tripartita var. mollissima - Minerva Rentería-Ortega; María de Lourdes Colín-Alvarez; Víctor Alfonso Gaona-Sánchez; Mayra C. Chalapud; Alitzel Belém García-Hernández; Erika Berenice León-Espinosa; Mariana Valdespino-León; Fatima Sarahi Serrano-Villa; Georgina Calderón-Domínguez (Membranes, 2023)
The inadequate management of organic waste and excessive use of plastic containers cause damage to the environment; therefore, different studies have been carried out to obtain new biomaterials from agricultural subproducts. The objective of this work was to evaluate the feasibility of using the pectin extracted from the peel of Passiflora tripartita var. mollissima (PT), characterizing its type and viability for the production of edible biodegradable films. In addition, films of two thicknesses (23.45 ± 3.02 µm and 53.34 ± 2.28 µm) were prepared. The results indicated that PT is an excellent raw material for the extraction of pectin, with high yields (23.02 ± 0.02%), high galacturonic acid content (65.43 ± 2.241%), neutral sugars (ribose, xylose, glucose) and a high degree of esterification (76.93 ± 1.65%), classifying it as a high-methoxy pectin. Regarding the films, they were malleable and flexible, with a water vapor permeability from 2.57 × 10−10 ± 0.046 to 0.13 × 10−10 ± 0.029 g/s mPa according to thickness, being similar to other Passiflora varieties of edible films. The pectin extraction yield from PT makes this fruit a promising material for pectin production and its chemical composition a valuable additive for the food and pharmaceutical industries.